IMPLEMENTASI ASAS DISPENSASI KAWIN DI WILAYAH HUKUM PENGADILAN TINGGI AGAMA PALU PERSPEKTIF MASLAHAH - massadi, massadi (Jurisprudentie : Jurusan Ilmu Hukum Fakultas Syariah dan Hukum, 2018)
Abstract The results of the study revealed that the degree of election of marriage dispensation in the jurisdiction of the Religious High Court of Palu was motivated by several factors, namely the pregnancy occurrence, parents' concerns, economic, matchmaking, and culture when was about to get married and still under-age so it had to firstly apply for dispensation of marriage to the religious court in accordance with Act No. 1 of 1974, Article 7 Paragraph (1) and (2) Concerning Marriage jo Compilation of Islamic Law Article 15 Paragraphs (1) and (2). The application of marriage dispensation was submitted to the court, then will be on trial and judge’s consideration in granting marriage dispensation which was not bound by the single positive law yet it was a consideration of justice, legal sociology and benefits that emphasized the implementation of maslahah principle as well. Keywords: Marriage Dispensation, Judge, Maslahah. Abstrak Hasil penelitian menunjukkan tingginya elektabilitas dispensasi kawin di wilayah hukum Pengadilan Tinggi Agama Palu didorong beberapa faktor yakni terjadinya kehamilan, kekhawatiran orang tua, ekonomi, perjodohan dan budaya ketika akan melakukan pernikahan masih dibawah umur sehingga terlebih dahulu harus mengajukan permohonan dispensasi kawin ke pengadilan agama sesuai dengan undang-undang nomor 1 tahun 1974, Pasal 7 Ayat (1) dan (2) Tentang Perkawinan jo Kompilasi Hukum Islam Pasal 15 Ayat (1) dan (2). Permohonan dispensasi kawin yang diajukan ke pengadilan, kemudian akan di sidangkan dan pertimbangan hakim dalam mengabulkan dispensasi kawin tidak terikat dengan hukum positif saja namun juga pertimbangan keadilan, sosiologi hukum dan kemanfaatan yang mengdepankan implementasi asas maslahah. Kata Kunci: Dispensasi Kawin, Hakim, Maslahah